Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Auditor Pemerintah(Studi Pada Auditor Pemerintah Di Bpkp Perwakilan Jawa Tengah) - Naryanto, Lilik Jiwo, Drs. Yuli Tr Cahyono, M.M., Akt., CA (2016)
ABSTRACT The study aimed to understand influence of independency, leadership style, organization commitment, comprehension of good governance, and organization culture towards performance of government auditors. Data was obtained by spreading questionaires to the government auditors who work at BPKP of Central Java Representation Office. The questionaires were spreads to 50 respondents, but only 39 respondents which the data could be analyzed and processe. Data analysis of the study used multi-linear regression analysis by SPSS Windows Program version 15.0. The study is consisted of dependent and independent variables. The dependent variable is performance of government auditors, and the independent variables are independency, leadership style, organization commitment, comprehension of good governance and organization culture. The result shows that independency, leadership style, organization commitment, comprehension of good governance, and culture organization has positive influence toward performance of government auditors. The simultaneous test results that independency, leadership style, organization commitment, comprehension of good governance, and culture organization variable have collectively positive influence towards performance of government auditors. Keywords: independency, leadership style, organization commitment, comprehension of good governance, culture organization, and performance.